Seeds' oil as biolubricant - Mirghani, Mohamed Elwathig Saeed; Adewale, Ahmed Idris; Kabbashi, Nassereldeen Ahmed; Muyibi, Suleyman Aremu; Daoud, Jamal Ibrahim; Abimbola, Mikail Maryam (IIUM Press, 2011)
The increasing demands for oils both for human consumption and for other industrial applications has culminated into an increasing need to search for oils from nonconventional sources to augment the available ones and also to meet specific applications. Environmental concerns about synthetic non-biodegradable polymers have also encouraged efforts towards their substitution with fully or partially biodegradable polymers of semi-synthetic or bio-origin. The physic-chemical properties of vegetable oils and their structures were discussed in terms of their potentially future use as base oils biolubricants and additives.